UV absorption cross-sections of selected sulfur-containing compounds at temperatures up to 500 °C. (March 2015) - Grosch, H.; Fateev, A.; Clausen, S.
Abstract: The temperature dependence of the ultraviolet absorption cross-sections of three different sulfur containing compounds, hydrogen sulfide (H2 S), carbon disulfide (CS2 ) and carbonyl sulfide (OCS), are presented between 200 nm and 360 nm at a resolution of 0.018 nm. The absorption cross-sections for each compound are initially compared with those available in the literature, followed by the discussion of the measurements and their spectral features at three temperatures up to 500 °C/773 K. Uncertainties in the measured absorption cross-sections are also addressed. Abstract : Highlights: H2 S, CS2 and OCS/COS UV absorption cross-sections between 195 nm and 360 nm . Experimental measurements of temperature dependent absorption-cross sections up to 500 °C. Discussion of uncertainties in the measurements.